2011
DOI: 10.5581/1516-8484.20110073
|View full text |Cite
|
Sign up to set email alerts
|

Titers of ABO antibodies in group O blood donors

Abstract: BackgroundPlasma components of group O blood donations are rarely submitted to ABO antibody titrations even though it is well known that passively acquired antibodies may destroy the recipient's own red cells and tissue grafts.ObjectiveThus, group O donations stratified by gender and age were randomly titrated to identify the best source of products for apheresis and exsanguinous transfusion.MethodsSamples from 603 blood donors were tested by ABO antibody titration using the conventional tube technique at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
5
23
0
Order By: Relevance
“…Human blood samples are not uniform in their antibody composition, with different samples and blood types having different ratios and levels of IgG and IgM, each of which may show variations in avidity and affinity, and each of which may show further variances in specificity . Consistent with results cited elsewhere we observed significant ranges in antibody activity between individual samples. Of particular relevance to the ABO system are antibody specificity variances that can detect the same or similar antigens.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Human blood samples are not uniform in their antibody composition, with different samples and blood types having different ratios and levels of IgG and IgM, each of which may show variations in avidity and affinity, and each of which may show further variances in specificity . Consistent with results cited elsewhere we observed significant ranges in antibody activity between individual samples. Of particular relevance to the ABO system are antibody specificity variances that can detect the same or similar antigens.…”
Section: Discussionsupporting
confidence: 89%
“…The importance of reducing ABO antibodies to low levels is an established prerequisite for ABOiKT . As seen in our results and also well established in the literature, natural levels of ABO antibodies, especially for group O individuals, predominantly exceed ABOiKT transplant criteria with titers greater than 16. It is therefore necessary that procedures be undertaken to reduce ABO antibody levels until deemed low.…”
Section: Discussionsupporting
confidence: 84%
“…These data may be useful for anticipating the impact of donor demographic variables on the prevalence of high‐titer ABO in PLT inventory. The correlation between ABO antibody titer levels and age of donors has been previously described . Our results suggest that a strategy reducing the number of group O PLT donations from females under 30 years old may also reduce the risk of hemolysis from ABO‐incompatible plasma containing PLT transfusion, but this strategy may negatively impact the PLT donor pool already strained by TRALI mitigation strategies …”
Section: Discussionsupporting
confidence: 71%
“…After demonstration that group 0 healthcare workers were less likely to become infected with SARS-CoV (62) A recent publication showed that the odds ratio for acquiring COVID-19 is higher in blood group A than in blood group 0 (67). COVID-19 has more severe clinical presentations and outcome in elderlies and in males : intriguingly, elderly males are known to experience reductions in isoagglutinin titers (68,69). Studies are hence ongoing to evaluate correlations between isoagglutinin titers and outcome in blood group 0 and B patients.…”
Section: Side Benefits From Cp In Covid-19mentioning
confidence: 99%